Local (Malaysian) leech as alternative healing treatment and an Islamic perspective - Zulhisyam Abdul Kari @ Abdullah,; Ahmad Zaki Amiruddin,; Mohd Hafiz Jamaludin,; Lee, Seong Wei; WanYusoff Wan Shaharuddin, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
The therapy is known from the time of extreme antiquity, dating back more than 2,500 years ago and still being practiced nowadays. This fact testifies to its efficiency in various health problems. In some cases, traditional medical practitioners use leeches for therapeutic healing treatment which is known as ‘cupping’. Such remedial method is quickly gaining acceptance amongst the local folks which is now becoming a thriving business. Some have made this treatment as their main business even though the therapy is quite recent for people in this country. This article discusses the process of cupping by using leech in the Islamic perspective and also the uniqueness of the hirudin protein in leeches respectively.